Rifampicin-induced Pancytopenia in Pulmonary Tuberculosis Patient: A Rare Presentation - Yashika Bansal; Nitin Tangri (Journal of Clinical and Diagnostic Research, 2024)
Tuberculosis (TB) is prevalent throughout the world and is a major public health problem in most developing countries. In India, standardised and Directly Observed Treatment (DOT) under National Tuberculosis Elimination Programme (NTEP) is being recommended currently for drug-sensitive pulmonary TB. TB being a major health issue in developing nations like India, causes enormous death and morbidity every year. Anti-Tuberculosis Treatment (ATT) given for TB has been highly effective in fighting the disease and is generally well tolerated, with few minor side-effects. We report a 76-year-old male who was diagnosed with pulmonary TB and was on first-line four-drug anti-tubercular therapy ATT since seven days. He presented to the emergency department with loss of weight and appetite, chest tightness and vomiting. Liver Function Tests (LFT) was deranged, suggesting ATT-induced hepatitis. After normalisation of LFT, rifampicin reintroduction was initiated. Complete Blood Count (CBC) revealed pancytopenia. In bone marrow biopsy, normoblastic maturation with few micronormoblasts and megaloblast picture was seen that did not reveal any granuloma, thereby ruling out the presence of Mycobacterium tuberculosis (MTB). Iron profile and vitamin B12 levels were within normal limits. Rifampicin-induced pancytopenia is rare but its possibility should always be kept in mind while treating with ATT.